Ecological consequences of colony structure in dynamic ant nest networks. Issue 4 (24th January 2017) - Ellis, Samuel; Franks, Daniel W.; Robinson, Elva J. H.
Abstract: Access to resources depends on an individual's position within the environment. This is particularly important to animals that invest heavily in nest construction, such as social insects. Many ant species have a polydomous nesting strategy: a single colony inhabits several spatially separated nests, often exchanging resources between the nests. Different nests in a polydomous colony potentially have differential access to resources, but the ecological consequences of this are unclear. In this study, we investigate how nest survival and budding in polydomous wood ant ( Formica lugubris ) colonies are affected by being part of a multi‐nest system. Using field data and novel analytical approaches combining survival models with dynamic network analysis, we show that the survival and budding of nests within a polydomous colony are affected by their position in the nest network structure. Specifically, we find that the flow of resources through a nest, which is based on its position within the wider nest network, determines a nest's likelihood of surviving and of founding new nests. Our results highlight how apparently disparate entities in a biological system can be integrated into a functional ecological unit. We also demonstrate how position within a dynamic network structure can have important ecological consequences. Abstract : In this study we combine survival models with dynamic network analysis to show that the position of a wood ant nest in a multi‐nest network significantly effects the nest likelihood of surviving and founding new nests. This demonstrates network structure and position can have significant ecological consequences.